2017
DOI: 10.1177/1179556517720675
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry in Asthma Care: A Review of the Trends and Challenges in Pediatric Practice

Abstract: Background:Given the rising incidence of noncommunicable diseases (NCDs) globally, especially bronchial asthma, there is the need to reduce the associated morbidity and mortality by adopting an objective means of diagnosis and monitoring.Aim:This article aims to review the trends and challenges in the use of spirometry for managing childhood bronchial asthma especially in developing countries.Methods:We conducted a literature search of published data on the use of spirometry for the diagnosis of childhood bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Different diagnostic criteria for asthma, lack or variable access to care, lack of access to asthma guidelines, and sub-optimal access to asthma controller medications may contribute to the variations in reported asthma prevalence and severity between centers in our study, and as previously reported. 6,14 The high and varying prevalence of severe asthma especially among those with current asthma may be affected by similar factors and may equally reflect lack of diagnosis or lack of affordable controller therapy or spacer devices to enable effective delivery of medication. 15 Several environmental factors were highly prevalent and were associated with asthma or severe disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different diagnostic criteria for asthma, lack or variable access to care, lack of access to asthma guidelines, and sub-optimal access to asthma controller medications may contribute to the variations in reported asthma prevalence and severity between centers in our study, and as previously reported. 6,14 The high and varying prevalence of severe asthma especially among those with current asthma may be affected by similar factors and may equally reflect lack of diagnosis or lack of affordable controller therapy or spacer devices to enable effective delivery of medication. 15 Several environmental factors were highly prevalent and were associated with asthma or severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…This was a cross-sectional study of African adolescents aged [13][14] years who participated in ISAAC III in African centers, between January 2001 and November 2002. Active or passive consenting processing were done to obtain consent from parents and school authorities, according to local ethical guidelines while assent was obtained from participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of objective tests to support the diagnosis of asthma has contributed to inappropriate over diagnosis, under diagnosis and misdiagnosis of asthma among school children in Canada ( Yang et al, 2017 ). Ayuk et al (2017b) in their review observed that spirometry is currently under-used in both tertiary and primary care settings in resource poor countries, which was attributed to lack of institutional guidelines for asthma management, lack of spirometers and, where available, healthcare workers were improperly trained to use the tools and interpret the findings appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary function tests can be used as an aid in helping to diagnose, evaluate, monitor, and follow up pediatric patients with respiratory diseases as well as for assessing the effects of therapeutic interventions . Among the variety of possibilities, spirometry is the most commonly used pulmonary function test for assessing children with suspected or established respiratory conditions and for monitoring normal lung growth in healthy children.…”
Section: Introductionmentioning
confidence: 99%